2006
DOI: 10.1242/jcs.02758
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced osteogenesis is negatively regulated by Runx2/Cbfa1 serine phosphorylation

Abstract: Glucocorticoid hormones have complex stimulatory and inhibitory effects on skeletal metabolism. Endogenous glucocorticoid signaling is required for normal bone formation in vivo, and synthetic glucocorticoids, such as dexamethasone, promote osteoblastic differentiation in several in vitro model systems. The mechanism by which these hormones induce osteogenesis remains poorly understood. We demonstrate here that the coordinate action of dexamethasone and the osteogenic transcription factor Runx2/Cbfa1 synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 72 publications
6
76
0
1
Order By: Relevance
“…It is expressed in response to GCs A Clark Anti-inflammatory functions of glucocorticoid-induced genes Page 18 of 53 in a wide variety of cell types including mast cells (Kassel et al, 2001), monocytes or macrophages (Abraham et al, 2006;Aeberli et al, 2006;Bhattacharyya et al, 2007;Chen et al, 2002;Zhao et al, 2005), microglia (Zhou et al, 2007), T lymphocytes , dermal, lung and synovial fibroblasts (Phillips et al, 2006;Toh et al, 2004;Yang et al, 2006), endothelial cells (Furst et al, 2007), osteoblasts (Engelbrecht et al, 2003;Leclerc et al, 2004), keratinocytes (Onda et al, 2006;Stojadinovic et al, 2006), adipocytes (Bazuine et al, 2004), lung epithelial cells (Chivers et al, 2006;Hermoso et al, 2004), airway smooth muscle cells (Issa et al, 2007) and HeLa cells (Imasato et al, 2002;Lasa et al, 2002). Typically expression is quite rapid (within one hour), sustained (up to 24 hours), requires relatively low concentrations of GC, and is blocked by the GR antagonist RU486.…”
Section: Dusp1mentioning
confidence: 99%
“…It is expressed in response to GCs A Clark Anti-inflammatory functions of glucocorticoid-induced genes Page 18 of 53 in a wide variety of cell types including mast cells (Kassel et al, 2001), monocytes or macrophages (Abraham et al, 2006;Aeberli et al, 2006;Bhattacharyya et al, 2007;Chen et al, 2002;Zhao et al, 2005), microglia (Zhou et al, 2007), T lymphocytes , dermal, lung and synovial fibroblasts (Phillips et al, 2006;Toh et al, 2004;Yang et al, 2006), endothelial cells (Furst et al, 2007), osteoblasts (Engelbrecht et al, 2003;Leclerc et al, 2004), keratinocytes (Onda et al, 2006;Stojadinovic et al, 2006), adipocytes (Bazuine et al, 2004), lung epithelial cells (Chivers et al, 2006;Hermoso et al, 2004), airway smooth muscle cells (Issa et al, 2007) and HeLa cells (Imasato et al, 2002;Lasa et al, 2002). Typically expression is quite rapid (within one hour), sustained (up to 24 hours), requires relatively low concentrations of GC, and is blocked by the GR antagonist RU486.…”
Section: Dusp1mentioning
confidence: 99%
“…Furthermore, recent studies have reported promising results for this factor as a therapeutic transgene in orthopedic tissue engineering applications (16,17). Importantly, we have previously shown that retroviral overexpression of Runx2 reprograms nonosteoblastic dermal fibroblasts into a mineralizing, osteoblast-like phenotype in vitro and in vivo (18)(19)(20). Here we demonstrate that a continuous bone-soft tissuemimetic interface can be engineered by a simple, one-step seeding of primary dermal fibroblasts onto polymeric scaffolds containing a graded distribution of immobilized Runx2 retrovirus.…”
mentioning
confidence: 96%
“…37) Dipsaci Radix, a regimen to treat bone fractures or diseases over long periods in traditional Korean medicine can be used in regenerative medicine without serious side effects like those of DEX. DR DM and hederagenin 3-O-(2-O-acetyl)--L-arabinopyranoside increased important bone markers to a degree comparable to DEX, the representative osteogenic factor, but the precise mechanisms of osteoblast differentiation by DR DM and hederagenin 3-O-(2-O-acetyl)--L-arabinopyranoside are unknown.…”
Section: Discussionmentioning
confidence: 99%